Characteristics of Giant Viruses: Achantamoeba polyphaga Mimivirus, Pandoravirus and Tupanvirus: A Review of the Literature - Maya Amini Sukma; Tsabitna Amalia Ihsania; Cahya Arsya Luthfi (Indonesian Journal of Engineering and Technological Innovation, 2025)
'Giant viruses' are viruses that have a genome of >200,000 bp and have been shown to infect eukaryotic organisms such as algae and protists. Giant viruses viruses have unique characteristics in addition to being very large in size, these viruses have a complex genome structure so that they are able to reproduce independently in the host cell. independently in the host cell. Some of these viruses are Achantamoeba polyphaga Mimivirus, Pandoravirus and Tupanvirus. This review aims to summarize the research that has been done on the giant viruses that have been have been discovered. Methods used in writing this article were analyzed through searches on scientific databases such as PubMed, ScienceDirect and Google Scholar.